Vastos subúrbios da nova capital: formação do espaço urbano na primeira periferia de Belo Horizonte - Tito Flavio Rodrigues de Aguiar (2006)
Between 1891 and 1898, the state government moved the capital of Minas Gerais in order to unite the diverse state regions, and to promote regional modernization. The construction of a new capital, the Cidade de Minas, today Belo Horizonte, was originally conceived to create an urban center to foster state modernization through industrialization. Aarão Reis designed the plan of the Cidade de Minas in 1895. According to regional modernization project, the city was organized in elaborate technical bases, with up-to-date municipal services and public utilities, which were very sophisticated for the late nineteenth century Brazil. Aarão Reis planned the new capitals suburbs as a transition between the country and the city, with particular design connecting urban core and rural zone. That plan was not followed out in suburbs, and soon was replaced by another initiative of state government, also directed toward regional modernization: the creation of the colonial zone in 1898 and 1899. This settlement combined a governmental project of economic growth and agrarian modernization to Cidade de Minass urban project.The results of these modernizing enterprises had been different. By 1920, Belo Horizonte already was the center of the most dynamic and prosperous region of Minas Gerais, based upon city's industrialization and its hinterland's economic growth. But colonial zone of Belo Horizonte failed as agrarian modernization enterprise. In 1911, when the colonial zone had been released from governments control, suburban colonies were fair prosperous agricultural establishments. In 1912, the incorporation to suburban zone of the so called ex-colônias did not immediately transform these agricultural spaces in citywards. However, in the 1920s, areas of the suburban colonies next to urban core had faced processes of transformation that had converted the rural space into suburban space. With the growth of Belo Horizonte, in the 1920s and 1930s, the forming of first peripherys spaces was made in three different ways. First, spaces of suburban zone settled according to Aarão Reiss design became densely peopled as great suburban lots were parceled out. Second, rural spaces of old agricultural colonies had been converted into suburban spaces by division of colonial lots. Third, farms were divided in the rural zone, originating several vilas without urban infrastructure, beyond the boundary laid out in 1895 to the Cidade de Minas. In the 1920s, the urban growth was disorderly, without municipalitys control and chiefly promoted by private developers. Then appeared demands for rules to manage the pace of urban growth. In the 1930s, the process of planning of the city was initiated again, although in very little solid bases and not connected with the projects of regional modernization that had continued to be promoted by state government.